1995
DOI: 10.1016/0092-8674(95)90104-3
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the murine homeobox gene Cdx1 affects axial skeletal identities by altering the mesodermal expression domains of Hox genes

Abstract: Cdx1 is expressed along the embryonic axis from day 7.5 postcoitum until day 12, by which time the anterior limit of expression has regressed from the hindbrain level to the forelimb bud region. To assign a functional role for Cdx1 in murine embryonic development, we have inactivated the gene via homologous recombination. Viable fertile homozygous mutant mice were obtained that show anterior homeotic transformations of vertebrae. These abnormalities were concomitant with posterior shifts of Hox gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
333
3
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 329 publications
(365 citation statements)
references
References 52 publications
25
333
3
4
Order By: Relevance
“…The phenotype of Cdx1 À/À mice has already been reported, except for the gut (Subramanian et al, 1995), and we confirmed here the loss of Cdx1 expression in the intestinal epithelium by reverse transcription (RT)-PCR and immunohistochemistry ( Figure 1). Next, we produced Vil-Cdx1 transgenic mice (lines no.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The phenotype of Cdx1 À/À mice has already been reported, except for the gut (Subramanian et al, 1995), and we confirmed here the loss of Cdx1 expression in the intestinal epithelium by reverse transcription (RT)-PCR and immunohistochemistry ( Figure 1). Next, we produced Vil-Cdx1 transgenic mice (lines no.…”
supporting
confidence: 89%
“…In conclusion, despite its important role in anteroposterior patterning of the body axis (Subramanian et al, 1995) Cdx1 is dispensable for intestinal development and homeostasis. During intestinal carcinogenesis, Cdx1 overexpression may increase the severity of malignancy at least transiently at early stages in the case of small intestinal tumours, before being lost in advanced tumours by promoter hypermethylation and allelic loss (Domon-Dell et al, 2003;Pilozzi et al, 2004).…”
Section: Cdx1 In Mouse Intestinal Development and Cancer C Bonhomme Ementioning
confidence: 91%
See 1 more Smart Citation
“…The caudal-type transcription factors interact with HOX genes to generate the anterior-posterior axis, and viable homozygous cdx1 knockout mice were shown to have anterior homeotic transformations of vertebrae concomitant with posterior shifts of hox gene expression in the somatic mesoderm. 24 The effect of haploinsufficiency of this gene in humans is not known but altered precise temporal and spatial expression of genes such as the HOX genes during embryonic development is required for accurate skeletal modelling. 25 Unfortunately, material was not available for aCGH to identify the true extent of the deletions beyond the first exon in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the other two cases the deletion extended into the 3¢-UTR, and may therefore extend into downstream genes. Patient 8 presented with dysmorphic features consistent with a diagnosis of TCS, and was shown to have a deletion of exons [23][24][25][26], that removes the C-terminal region of treacle important for localisation to the nucleolus. Array CGH analysis suggested that the deletion did not extend into the downstream CD74 gene.…”
Section: Discussionmentioning
confidence: 99%